Utilization of E-Commerce and Innovation And Thus Their Impact on The Success of Culinary MSMES Businesses in East Medan: Pemanfaatan E-Commerce dan Inovasi Serta Dampaknya terhadap Keberhasilan Usaha UMKM Kuliner di Medan Timur - Jennifer Tantri; Afrizal Afrizal (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
Medan Timur District, covering an area of 8.89 km² with a population of 117,035, serves as a hub for informal economic growth, particularly in the diverse and innovative culinary MSME sector. The shift in consumer behavior toward online shopping via platforms such as GoFood, GrabFood, and ShopeeFood poses challenges for culinary MSMEs due to limitations in technology, digital marketing knowledge, and online business management, which reduce competitiveness and market opportunities. This study aims to examine the impact of e-commerce utilization and innovation on the success of culinary businesses in Medan Timur and provide practical recommendations to support MSME sustainability. The research employs a quantitative descriptive method with a population of 350 culinary MSME actors and a sample of 187 respondents determined using Slovin’s formula with a 5% margin of error. The results indicate that both partially and simultaneously, e-commerce utilization and innovation have a significant effect on business success.